National Accounts Revisions and Output Gap Estimates in a Model of Monetary Policy with Data Uncertainty - Lavan Mahadeva; Alex Muscatelli (Bank of England, External Monetary Policy Committee Unit, 2005)
This paper looks at some implications of data uncertainty for monetary policy. We combine national accounts data revisions with optimal control and filtering experiments on a calibrated model to discuss policy implications of price-versus-volume data uncertainty in GDP data for the United Kingdom. We find some degree of negative correlation between revisions to real GDP and GDP deflator data. We develop a methodology for estimating the output gap which takes account of the benefit of hindsight and decreasing measurement errors through time. Our optimal control experiments reveal that monetary policy makers would be led to place greater weight on nominal GDP data and correspondingly less weight on separate, uncertain estimates of prices and volume growth. However, estimates of real growth and also the output gap matter even when there is much uncertainty of this type. Our results also suggest that estimates of the level of inflationary pressure and nominal GDP data become more important when the economy is prone to inflationary overreactions to shifts in technological progress
Keywords: E01; E52; 330